Online privacy laws : European Union & select foreign countries - William, Ethan P. (Privacy and identity protection., 2013)
These reports describe the data protection laws of the European Union (Part I) and of selected foreign countries (Part II). They describe the legal framework for the collection, use, and transfer of data, and examine whether existing laws are adequate to deal with online privacy in an era of rapid technological development and globalization.